(untitled) (Studia Prawnicze / The Legal Studies, 1985)
The emergence of separate assets of the partnership, besides the assets of individual partners as a result of a contract, causes many complications in relations within the partnership and between it and third ’persons also in the field of liability. A debt of the partnership is a special kind of joint debt which can be settled only with the participation of all partners. They are also jointly obliged to discharge an obligation. Thus, in this case the debt differs from an ordinary joint and several debt, where all debtors are separately obliged to discharge an obligation and it can be done by each of the debtors, some of them or all of them. The debt of the partnership should really be called a joint debt. All partners are responsible for the debt of the partnership by means of separate assets of the partnership and their individual assets. Joint and several liability resulting from the law may be introduced by a provision of ius cogens or ius dispositivurn character. From- among numerous provisions of the civil code providing for joint responsibility only the provisons of art. art. 370, 380 § 2 and 881 have iuris divositivi character. The remaining provisions introducing joint liability, including art. 864 of the civil code, have iuri eogentis character. This means that it is not possible to exclude joint liability of partners by means of agreement between them and the creditor. If the debt has been settled by one of the partners, the obligation of the partnership ceases. However, recurrent claim on behalf of that partner arises against other partners. It may be satisfied in the first place from the joint assets and if it is insufficient, from individual assets of the partners. A special situation occurs in case of liability for the debt of the partnership resulting from a wrongful act as art. 441 of the civil code is then applied and recurrent claims are to be settled in accordance with this provision